Chemical Contracting Strategy Selection at PT CPI by Using Analytical Hierarchy Process - Syukirman, .; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2015)
Abstract - Oilfield chemicals are absolutely needed in oil industry to treat production fluid to produce quality oil and water. Without chemical treatment, the oil and water product cannot achieve its specification quality for shipping to customer. Therefore, the delivery and quality of chemical are very critical to the company’s business continuity. Chemicals are supplied by the company by using a contract. In developing a chemical contract, contracting strategy is one of critical step that will determine the contract execution. In order to ensure that the contract can be performed successfully, company must select the most appropriate contract strategy. Currently, there is no such standardize method in analyze the factors that influenced the contracting strategy and also there is no formal method in selecting the most suitable strategy. Contracting strategy may change after time based on the current business situation faced by the company. Hence, it is need to establish a baseline for contracting strategy selection that can be used as a guideline for contracting process for chemical in the future. This research is aimed to develop a decision making model for chemical contracting strategy. The strategy selection for chemical contract, both scope of work allocation and compensation method can be described as a multiple criteria decision making process. In this case, the decision maker must find the alternative solution by considering multiple and under conflicting criteria. Analytic Hierarchy Process (AHP) is an ideal method for such case. The AHP is started with relevant decision criteria identification through literature review and brainstorming with stakeholder. After relevant criteria determined, then pair-wise comparison was conducted by several respondents to get decision criteria prioritization. Several alternative solutions were then generated and ranked and the data processed using Expert Choice software to get the best alternative. The research results some decision criteria for chemical contracting strategy. After prioritizing decision criteria and assess some alternatives, it can be concluded the most appropriate alternative. For scope of work allocation, the most appropriate alternative is a split contract between chemical and industrial salt, with the criterion which has the major contribution is contract continuity. This alternative will ensure the continuity of contract and therefore the business sustainability. For compensation method, the most appropriate alternative is unit price with incentive, with contractor incentives to deliver quality chemical criteria has the major contribution. This alternative will ensure the contractor to deliver the best quality of chemical with cost effective. It was also found that AHP model is suitable for multicriteria decision making and allows the team to structurally put weights into decision criteria by a simple pair-wise comparison. It is also allows a group decision making by involving several participants and the result could be summarized to reach consensus.Keywords: Contracting strategy, oilfield chemical, Analytic Hierarchy Process